2018
DOI: 10.31248/jasvm2017.068
|View full text |Cite
|
Sign up to set email alerts
|

Effect of graded levels of ginger rhizome (Zingiber officinale) meal on serum biochemistry of pubertal New Zealand White rabbits

Abstract: Forty-eight sexually matured (7 to 8 months old) healthy male and female New Zealand White rabbits were used to determine the effect of graded levels of ginger rhizome meal on serum biochemical indices. The rabbits were divided into 4 treatment groups, namely T1, T2, T3 and T4 and assigned to four treatment diets in a Complete Randomized Block Design (CRBD). Each of the treatment groups consisted of 12 rabbits (6 does and 6 bucks) replicated 3 times with 2 rabbits per replicate. The levels of inclusion of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
0
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 7 publications
4
0
2
Order By: Relevance
“…Aspartate transaminase values obtained in this study were within the range of 10-120 (iu/L) reported by the University of Pennsylvania School of Veterinary Medicine (2002). However, the AST values obtained in this study were higher than the range of 7.73-16.0 (iu/L) reported with sundried, ensiled and fermented cassava peel based diets, and higher than the range of 24.68-38.96 (iu/L) reported by Ilo and Egu (2018) for rabbits fed graded levels of ginger rhizome meal. Analysis of live enzymes (AST, ALT and ALP) activities give valuable diagnostic information for a number of disease conditions.…”
Section: Discussioncontrasting
confidence: 89%
See 4 more Smart Citations
“…Aspartate transaminase values obtained in this study were within the range of 10-120 (iu/L) reported by the University of Pennsylvania School of Veterinary Medicine (2002). However, the AST values obtained in this study were higher than the range of 7.73-16.0 (iu/L) reported with sundried, ensiled and fermented cassava peel based diets, and higher than the range of 24.68-38.96 (iu/L) reported by Ilo and Egu (2018) for rabbits fed graded levels of ginger rhizome meal. Analysis of live enzymes (AST, ALT and ALP) activities give valuable diagnostic information for a number of disease conditions.…”
Section: Discussioncontrasting
confidence: 89%
“…Alkaline phosphatase values obtained in this study were within the normal range of 17.00-192.00 (iu/L) reported by Merck (2012) for rabbits. However, the ALP values in this study were higher than the range of 5.92-8.38 (iu/L) reported by Ewuola et al (2010) for rabbits fed dietary prebiotics and probiotics, and higher than the range of 44.25-56.30 (iu/L) as reported by Ilo and Egu, 2018, for rabbits fed graded levels of ginger rhizome meal. This disparity may be associated with the differences in physiological and nutritional status of the rabbits.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations